MRI and CT findings of cryptococcal vaginitis - Ranganathan, S.; Moosa, F.; Kamarulzaman, Adeeba; Looi, L.M. (British Institute of Radiology, 2005)
Cryptococcus neoformans is a yeast like fungus, which is commonly found in bird droppings, especially pigeons. Most cases of cryptococcal infections occur in immunocompromised patients or in those who are on long term immunosuppressant therapies. Cryptococcal infection usually presents as a meningoencephalitis or a pulmonary infection. Skin; bone and genital infections are very rare. We report the second case of vaginal cryptococcossis to be reported in English literature and the first to be imaged with CT and MRI.